2010
DOI: 10.1007/s11481-010-9213-z
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol-Induced Interactive Phosphorylation of Src and Toll-like Receptor Regulates the Secretion of Inflammatory Mediators by Human Astrocytes

Abstract: Secretion of pro-inflammatory molecules by astrocytes after alcohol treatment was shown to be associated with neuroinflammation. We hypothesized that activation of cytosolic phospholipase A2 (cPLA2) and cyclooxygenase (COX-2) by ethanol in astrocytes enhanced the secretion of inflammatory agents via the interactive tyrosine phosphorylation of toll-like receptor 4 (TLR4) and Src kinase. To test this hypothesis, we treated primary human astrocytes with 20 mM ethanol Correspondence to: James Haorah, jhaorah@unmc.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 43 publications
1
36
0
2
Order By: Relevance
“…Activation of TLR4 causes hyperalgesia (Calil et al, 2014; Watkins et al, 2009). Importantly, alcohol exposure can increase TLR4 expression and TLR4-facilitated secretion of pro-inflammatory mediators (Corrigan and Hutchinson, 2012; Floreani et al, 2010). One study has shown that the activation of DORs through mechanisms involving β-arrestin2 inhibit TLR4-induced release of tumor necrosis factor induced by the TLR4 agonist lipopolysaccharide in mast cells (Madera-Salcedo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of TLR4 causes hyperalgesia (Calil et al, 2014; Watkins et al, 2009). Importantly, alcohol exposure can increase TLR4 expression and TLR4-facilitated secretion of pro-inflammatory mediators (Corrigan and Hutchinson, 2012; Floreani et al, 2010). One study has shown that the activation of DORs through mechanisms involving β-arrestin2 inhibit TLR4-induced release of tumor necrosis factor induced by the TLR4 agonist lipopolysaccharide in mast cells (Madera-Salcedo et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 and TLR4 signaling is important in these processes as demonstrated by the fact that neutralizing antibodies to IL-1R and TLR4 can suppress ethanol induction of these proinflammatory molecules and signaling pathways (Blanco et al, 2005). TLR4 was also shown to be critical in ethanol induction of Cox-2 and Src phosphorylation in astrocytes (Floreani et al, 2010). These observations suggest that ethanol induction of immune responses in the CNS occurs through the movement of these receptors to lipid rafts, resulting in the activation of signaling pathways that ultimately lead to the production of proinflammatory molecules.…”
Section: Link Between Ethanol and Immune Responsesmentioning
confidence: 99%
“…Other agents such as lipopolysaccharides (LPS) can stimulate cPLA2 and PGE2 production through an ERK1/2-dependent pathway in astrocytes [58]. In fact, a number of other stimuli, including ammonia [59], alcohol [60], ceramide [61], bradykinin [62, 63], and diethylmaleate/iodoacetate [64] have been shown stimulate cPLA 2 and engage in astrocytic inflammatory and oxidative pathways.…”
Section: Cpla2 In Oxidative and Inflammatory Signaling Pathways In Asmentioning
confidence: 99%